Knowledge transfer inside the regional economic system: the case of eighty years of economic history of the Russian North-East - Alexander Pelyasov; Nataliya Galtseva; Igor Batsaev; Igor Golubenko (European Regional Science Association (ERSA), 2011)
Economic role of the knowledge transfer is studied on the example of the Russian North-East and its two basic branches that is exploration and mining which form the core of the regional economy (regional mining system). Russian North-East can be considered as isolated industrial district with the basic gold mining activity. The scale of this activity has been determined regional socio-economic development for the last 80 years. The major information for this study has been taken from GIS on the spatial structure of exploration and mining branches in the Russian North-East on the district level for the last 80 years. On the basis of revealed regularities and specifics in the interregional knowledge transfer we have formed general understanding of this process. We have analyzed major channels of knowledge transfer from exploration as the branch generating new knowledge on the mineral resources to mining in which this knowledge is utilized. We have determined major systems of knowledge transfer from one branch to the other under different periods of regional economic history. We have examined how territorial structures of exploration and mining industries had been changed inside the regional system for the last 80 years. Main characteristics of knowledge transfer inside the regional mining system influence its productivity (volume of extraction, speed of development of the new deposits, etc.). Effective communication between exploration and mining industry, knowledge transfer from the geologists to the miners is critically important for the sustainable work of the regional mining system.
Keywords: 330